Technology in Mathematics teaching: the pros and cons - Md Khambari, Mas Nida; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi (Elsevier, 2010)
This paper centers on the use of laptop by Mathematic teachers at 28 secondary schools in Malaysia. It addresses some benefits and challenges faced by the teachers in integrating technology into Mathematics teaching-learning process, as well as their daily activities related to the process such as the use of resources, and the preparation and planning of lesson. A survey was carried out among 172 teachers who were currently teaching the subject area to get their views on laptop use. Although teachers experience challenges in using laptop for Mathematics teaching, they also gained much benefit from it. The survey findings might be useful for the Ministry of Education in developing continuing professional development courses and trainings for teachers. Hence, teachers would be better equipped with the appropriate knowledge, skills, and resources, to support them in their teaching-learning process in the classroom.